2017
DOI: 10.1093/ecco-jcc/jjx104
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoles Promote Anti-TNF Mediated Induction of Regulatory Macrophages and Enhance Therapeutic Efficacy in a Murine Model

Abstract: Background and AimsRegulatory macrophages play a critical role in tissue repair, and we have previously shown that anti-tumour necrosis factor [TNF] antibodies induce these macrophages in vitro and in vivo in IBD patients. The induction of regulatory macrophages can be potentiated using the combination of anti-TNF and thiopurines, consistent with the enhanced efficacy of this combination therapy described in clinical trials. As thiopurines are unfortunately associated with significant side effects, we here aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…We have previously shown that the T-cell transfer colitis model responds to anti-TNFmAb therapy in a dose-dependent fashion 23. In this titration experiment, intestinal IL-10 levels were increased in animals treated with the effective dosage of anti-TNF (figure 3A).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…We have previously shown that the T-cell transfer colitis model responds to anti-TNFmAb therapy in a dose-dependent fashion 23. In this titration experiment, intestinal IL-10 levels were increased in animals treated with the effective dosage of anti-TNF (figure 3A).…”
Section: Resultsmentioning
confidence: 61%
“…Similarly, in a recent experiment with a small molecule kinase inhibitor, we observed almost complete mucosal healing without any effect on IL-10 expression in the same model (ME Wildenberg, personal communication 2019). In contrast, when we performed an unbiased drug screen for drugs that enhanced the anti-TNF-induced CD206+ regulatory macrophage polarisation, we identified albendazole as a drug that potentiates the effect of anti-TNF in vitro and in vivo 23. We found that albendazole specifically synergised with anti-TNF in upregulating IL-10 expression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the effects of benzimidazole derivatives to host immunity are noted in the literature. Wildenberg et al reported that six benzimidazole derivatives induced regulatory macrophages (Wildenberg et al, 2017). Rickard et al reported that the benzimidazole diamide GSK 669 inhibits NOD2, an intracellular pattern recognition receptor involved in the induction of pro-inflammatory cytokines (Rickard et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that TNF was over-expressed in the intestinal mucosa and could lead apoptosis of the intestinal epithelial cells (IECs) in IBD. [44][45][46] However, anti-in ammatory cytokine IL-10 exerted essential functions to maintain tissue homeostasis during infection and in ammation through restriction of excessive in ammatory responses and promotion of tissue repairing mechanisms. 47,48 IL-10 could secreted by both immune cells and IECs.…”
Section: Discussionmentioning
confidence: 99%